Preparation method of corrosion-resistant titanium alloy foil for plate heat exchanger
Titanium alloy foil is prepared through vacuum induction smelting and multi-fire temperature pressure treatment, and an antibacterial and corrosion-resistant protective layer is formed on its surface, which solves the problems of complexity and high cost of processing of titanium alloy foil and realizes the harsh environment The long-term stability and corrosion resistance improve the performance of plate heat exchangers.
Patent Information
- Application Number
- CN202411281381.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-13
AI Technical Summary
The processing process of existing titanium alloy foils is complex and expensive, making it difficult to maintain long-term stability and corrosion resistance in harsh environments.
The titanium alloy ingot was prepared by vacuum induction smelting, and the multi-fire temperature pressure treatment was carried out and micro-etched to form micropores, deposition of boron oxide particles and coating mesoporous ceramic powder composite liquid loaded with octinibide to form antibacterial and resistant Corrode the protective layer and enhance the surface hardness by laser clad nickel layer.
It significantly improves the corrosion resistance and antibacterial properties of titanium alloy foil, extends the service life, reduces corrosion rate and wear, and improves the sanitary performance and operating efficiency of plate heat exchangers.
Smart Images

Figure CN119259682A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plate heat exchanger material processing, and in particular to a method for preparing a corrosion-resistant titanium alloy foil for a plate heat exchanger. Background Art
[0002] Bipolar plates are key components of proton exchange membrane fuel cells (PEMFCs), accounting for about 70% of the mass of the entire battery stack and about 40% of its cost; the titanium alloy substrate of the bipolar plate has the advantages of excellent corrosion resistance, higher specific strength, and light weight; plate heat exchangers may be exposed to various corrosive substances such as acids, alkalis, and salts during use, and the corrosion resistance of titanium alloy foil can ensure the long-term stable operation of the equipment in these environments. Titanium alloy foil has excellent mechanical properties such as high strength, high toughness, and high hardness, which enables it to maintain good stability and reliability in harsh environments such as high temperature and high pressure. The working environment of the plate heat exchanger may be relatively harsh, and the mechanical properties of titanium alloy foil can ensure that the equipment can perform well in various complex environments.
[0003] Bipolar plates can be roughly divided into three categories: carbonaceous materials, metal materials and metal-carbon composite materials; among them, aluminum, nickel, titanium and stainless steel and other metal materials can be used to make bipolar plates. Metal bipolar plates are easy to process, can be mass-produced, have low cost, are thin, and have high volume power and specific energy of the battery. The new Ti-Ni-Nb near-α titanium alloy has excellent corrosion resistance and is a good material for bipolar plate substrates. The thickness of titanium alloy foil used to make bipolar plates is generally 0.05-0.15mm, and the thickness deviation is required to be no more than ±5μm; but Ti-Ni-Nb foil generally needs to be processed on a twenty-roll mill, which has a complex processing process, a long processing cycle and high cost. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a method for preparing a corrosion-resistant titanium alloy foil for a plate heat exchanger.
[0005] The technical solution of the present invention is: a method for preparing a corrosion-resistant titanium alloy foil for a plate heat exchanger, comprising the following steps:
[0006] S1. Preparation of titanium alloy ingots
[0007] Weighing raw materials, and performing vacuum induction melting on the raw materials to obtain a titanium alloy ingot;
[0008] S2. Preparation of billet to be rolled
[0009] The ingot is heated to 480-520°C, kept warm for 30-60 minutes, and then subjected to multi-fire warm pressing treatment, with a total processing rate of 60-80%, to obtain a warm pressed blank, and the surface of the warm pressed blank is micro-etched to produce a plurality of micropores with an aperture of 0.01-0.03 mm on the surface, and then boron oxide particles are vapor-deposited inside the micropores, and a mesoporous ceramic powder composite liquid loaded with octenidine is coated on the surface of the warm pressed blank to obtain a preset oxide layer with a thickness of 0.03-0.05 mm, a protective atmosphere is introduced, and laser cladding and nickel plating are performed, and after completion, a blank to be rolled with a composite film layer on the surface is obtained;
[0010] During the laser cladding process: the processing power is 18-22W, the scanning speed is 500-700mm / s, the time is 15-18ns, and the loading amount of octenidine is 58-62%;
[0011] S3, cooling and cold rolling
[0012] The billet to be rolled is subjected to 3 to 8 passes of cooling cold rolling, with each pass cooling 30 to 50°C, each pass deformation of 15 to 40%, and vacuum annealing between each pass to obtain the rolled billet; the vacuum annealing temperature is 650 to 700°C, the time is 20 to 30 minutes, and the vacuum degree is 10 -2 ~10 -1 Pa,
[0013] S4. Post-processing
[0014] After rolling, the titanium alloy foil is straightened and the surface is cleaned.
[0015] Description: The micropores on the surface of titanium alloy provide physical anchor points for loading boron oxide and subsequent mesoporous ceramic powder solution, so that the solution can adhere more firmly to the surface of titanium alloy, improving the adhesion. Boron oxide particles have good corrosion resistance. By micro-etching and then depositing boron oxide particles and then coating the mesoporous ceramic powder composite solution loaded with octonidine, a protective layer with antibacterial and corrosion-resistant properties will be formed on the surface of titanium alloy foil. This protective layer can effectively prevent the direct contact between the corrosive medium and the titanium alloy foil and reduce the corrosion rate; at the same time, in the plate heat exchanger, octonidine can be more effectively released and attached to the surface of titanium alloy foil to form an antibacterial barrier, further preventing the growth and reproduction of corrosive bacteria, thereby enhancing the corrosion resistance of titanium alloy foil and improving the hygienic performance and operating efficiency of the heat exchanger. Titanium alloy foil may be subjected to various forces such as fluid scouring and vibration in the plate heat exchanger, resulting in wear. By coating the nickel layer, the surface hardness and wear resistance of the titanium alloy foil can be significantly improved, extending its service life.
[0016] Furthermore, the preparation method of the mesoporous ceramic powder composite liquid loaded with octenidine is as follows: dissolving octenidine in acetone at a ratio of 25 to 40 g: 400 to 600 mL to obtain an octenidine solution; then mixing the mesoporous ceramic powder and the octenidine solution at a mass ratio of 1 to 5: 0.5 to 0.7, and then electromagnetically stirring at a temperature of 30 to 35° C. for 23 to 25 minutes; the electromagnetic power is 25 to 40 W, the magnetic strength is 100 to 200 T, and the rotation speed is 200 to 500 r / min to obtain a mesoporous ceramic powder composite liquid loaded with octenidine;
[0017] Description: Mesoporous ceramic powder has a large specific surface area and pore volume, so it can provide abundant loading sites for octenidine, which may enhance its antibacterial effect. In addition, the mesoporous ceramic powder itself has certain adsorption properties, which can adsorb and fix octenidine molecules to prevent them from being quickly released or lost during use. This helps to maintain the concentration of octenidine at the site of action, thereby prolonging its antibacterial effect. The antibacterial effect of octenidine can also reduce the growth of microorganisms on the surface of titanium alloy foil, thereby improving the hygiene performance and operating efficiency of the heat exchanger.
[0018] Furthermore, the coating method is a coordinated process of spin coating and dip coating.
[0019] The method for the coordinated treatment of spin coating and dip coating is as follows: during the first 1 / 4 to 1 / 3 of the coating thickness, the micro-etched warm pressed blank is fixed on the tray of the spin coater, the spin coater is started and rotated at a first speed for 1 to 3 minutes, and at the same time, 1 / 3 to 1 / 2 of the mesoporous ceramic powder composite liquid loaded with octenidine is taken and dripped on the top of the blank at a flow rate of 3 to 5 mL / s, and after dripping, the spin coater is adjusted to rotate at a second speed for 2 to 5 minutes, and the first oxide layer is obtained by heating; wherein the first speed is 30 to 50 r / min, the second speed is 1500 to 2000 r / min, the heating temperature is 85 to 90° C., and the heating time is 5 to 10 minutes;
[0020] Then, the blank loaded with the first oxide layer is vertically immersed in the remaining mesoporous ceramic powder composite liquid loaded with octenidine, and vertically pulled up after standing for 20 to 25 seconds, and the dip coating is repeated 3 to 5 times to obtain a preset oxide layer;
[0021] Description: In the early stage of coating, the spin coating treatment can make the mesoporous ceramic powder composite liquid loaded with octenidine penetrate into the micropores of the titanium alloy foil, fill and partially seal these micropores, which helps to reduce the chance of corrosive media (such as water, oxygen, etc.) directly contacting the titanium alloy substrate, thereby improving its corrosion resistance. The coating formed by spin coating is often denser and more uniform, and can form a protective barrier on the surface of the titanium alloy foil to prevent the penetration of corrosive media. It can also combine with the titanium alloy substrate to enhance the adhesion of the coating, and can have an antibacterial effect on the basis of preventing the penetration of corrosive media.
[0022] Furthermore, a smoothing treatment is performed after each dip coating, and the smoothing treatment method is: flushing the surface of the blank with high-pressure nitrogen for 5 to 8 minutes, and then rinsing with deionized water for 2 to 4 times;
[0023] Note: High-pressure nitrogen flushing during the smoothing treatment may help to enhance the bonding force between the coating and the titanium alloy substrate, improve the density of the coating and reduce the peeling and cracking of the coating during subsequent use, thereby extending the service life of the coating and improving its corrosion resistance. The smoothing treatment not only helps to improve the appearance quality of the coating, but also may further improve the finish and smoothness of the coating by removing tiny bumps and depressions on the coating surface. This smoother surface is more conducive to the contact between octenidine and bacteria and exerting its antibacterial effect.
[0024] Further, in step S2, the method of the multi-fire warm pressing treatment is: continuously heating, and performing one pass of warm pressing treatment and keeping the temperature for 25 to 30 minutes when the temperature is raised to 70 to 80°C below the ingot β transformation temperature, 35 to 45°C below the β transformation temperature, 10 to 15°C below the β transformation temperature, 25 to 40°C above the β transformation temperature, and 50 to 60°C above the β transformation temperature, respectively, and performing one pass of multi-directional forging at each corresponding temperature to obtain the warm pressed billet;
[0025] The method of the warm pressing treatment is as follows: the pressing pressure is 450-550 MPa, the pressing time is 3-5 min, and the pressing method is bidirectional pressing or floating pressing;
[0026] Description: Multi-fire warm pressing treatment combined with multi-directional forging can make the internal structure of titanium alloy more uniform. Warm pressing treatment and multi-directional forging in each temperature range can help eliminate casting defects in the ingot, such as shrinkage and looseness, and make the distribution of alloy elements more uniform. The improvement of organizational uniformity helps to improve the mechanical properties and corrosion resistance of titanium alloy; warm pressing treatment below the β transformation temperature helps to maintain the good plasticity and deformation ability of titanium alloy; this makes the titanium alloy easier to deform in the subsequent processing, thereby improving the processing efficiency, and heating the titanium alloy to the above temperature and keeping it warm for a period of time can further improve the heat resistance and oxidation resistance of titanium alloy. The insulation aging treatment can refine and disperse the precipitated phase in the titanium alloy to form a more stable intergranular phase, thereby improving the oxidation resistance and heat resistance of the material; processes such as bidirectional pressing and floating pressing can improve the density and uniformity of the product, reduce internal defects and stress concentration, and thus improve the corrosion resistance of titanium alloy foil to a certain extent.
[0027] Furthermore, in step S1, during the vacuum induction melting, the vacuum degree in the vacuum melting furnace is ≤4.5Pa, the arc stabilization current is 1-3A, the melting voltage is 25-35V, the melting current is 3-5kA, and the melting time is 5-35min;
[0028] Note: Vacuum induction capacity under the above environment helps to ensure the smooth progress of the smelting process, reduce temperature fluctuations and uneven electromagnetic stirring in the molten pool, and help to obtain a more uniform and fine grain structure, thereby improving the mechanical properties and processing properties of titanium alloys.
[0029] Further, in step S2, the micro-etching process is laser micro-etching process, the laser energy is 1000-1200 mJ, the laser wavelength is 1050-1100 nm, and the pulse time is 12-16 ns;
[0030] Note: The micropores obtained by laser micro-etching under the above parameters are more stable and the etching is more efficient.
[0031] Further, in step S2, the vapor deposition parameters are: power of 5000-7000W, pressure of 180-200Pa, and electrode spacing of 400-550 mils;
[0032] Note: Vapor deposition under the above parameters helps to form a uniform and dense coating, improving the wear resistance, corrosion resistance and high temperature performance of titanium alloy foil.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] (1) The present invention forms a protective layer with antibacterial and corrosion-resistant properties on the surface of the titanium alloy foil by micro-etching and depositing boron oxide powder in the micropores, and then coating the surface of the titanium foil with a mesoporous ceramic powder composite liquid loaded with octenidine, thereby preventing the corrosive medium from directly contacting the titanium alloy foil and reducing the corrosion rate. At the same time, in the plate heat exchanger, the use of the mesoporous ceramic powder composite liquid loaded with octenidine as a coating helps to reduce the growth of microorganisms on the surface of the titanium alloy foil and improve the hygienic performance and operating efficiency of the heat exchanger. By coating the nickel layer, the surface hardness and wear resistance of the titanium alloy foil can be significantly improved, avoiding the wear of the titanium alloy foil caused by fluid scouring, vibration, etc. in the plate heat exchanger, and effectively extending its service life.
[0035] (2) The present invention utilizes the adsorption and corrosion resistance of mesoporous ceramic powder to further adsorb and fix octenidine molecules to prevent them from being quickly released or lost during use. A layer of mesoporous ceramic powder composite liquid loaded with octenidine is coated on the surface of the titanium alloy warm-pressed billet to enhance the antibacterial effect of the titanium alloy foil. This can achieve the purpose of maintaining the concentration of octenidine at the site of action, reducing the growth of microorganisms on the surface of the titanium alloy foil, prolonging its antibacterial action time, and improving the hygiene performance and operating efficiency of the heat exchanger.
[0036] (3) The present invention can use the synergistic effect of spin coating and dip coating to allow a small amount of mesoporous ceramic powder composite liquid loaded with octenidine to penetrate into the micropores of the titanium alloy foil in the early stage of coating, fill and partially seal these micropores, thereby reducing the chance of corrosive media directly contacting the titanium alloy foil, thereby improving its corrosion resistance. Subsequent dip coating can obtain a relatively dense and uniform coating. The composite coating obtained by the present invention not only further prevents the penetration of corrosive media but also has a high antibacterial effect, and has the advantage of improving the performance of the plate heat exchanger. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a comparison chart of the corrosion resistance of titanium alloy foils prepared in Examples 1 to 7 of the present invention and Control Groups 1 to 2;
[0038] Figure 2 It is a comparison chart of the corrosion resistance of titanium alloy foils prepared in Example 1, Examples 8 to 15 and Control Groups 3 to 5 of the present invention;
[0039] Figure 3 It is a comparison chart of the corrosion resistance of titanium alloy foils prepared by Example 1, Examples 16 to 19 and Control Group 6 of the present invention. DETAILED DESCRIPTION
[0040] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.
[0041] Embodiment 1: A method for preparing a corrosion-resistant titanium alloy foil for a plate heat exchanger, comprising the following steps:
[0042] S1. Preparation of titanium alloy ingots
[0043] Weigh 50 kg of raw materials and perform vacuum induction melting on the raw materials to obtain a titanium alloy ingot; during the vacuum induction melting, the vacuum degree in the vacuum melting furnace is 4.5 Pa, the arc stabilization current is 2 A, the melting voltage is 30 V, the melting current is 4 kA, and the melting time is 10 min;
[0044] S2. Preparation of billet to be rolled
[0045] The ingot is heated to 500°C, kept warm for 45 minutes, and then subjected to multi-fire warm pressing treatment with a total processing rate of 70% to obtain a warm pressed billet, and the surface of the warm pressed billet is micro-etched to produce a number of micropores with an aperture of 0.02 mm on the surface, and then boron oxide particles are vapor-deposited inside the micropores, and a mesoporous ceramic powder composite liquid loaded with octenidine is coated on the surface of the warm pressed billet to obtain a preset oxide layer with a thickness of 0.04 mm, a nitrogen protective atmosphere is introduced, and laser cladding and nickel plating are performed to obtain a billet to be rolled with a composite film layer on the surface.
[0046] The method of multi-fire warm pressing treatment is: continuously heating, and performing one pass of warm pressing treatment and keeping the temperature for 27 minutes when the temperature rises to 75°C below the ingot β transformation temperature, 40°C below the β transformation temperature, 13°C below the β transformation temperature, 32°C above the β transformation temperature, and 55°C above the β transformation temperature, respectively, and performing one pass of multi-directional forging at each corresponding temperature to obtain a warm pressed billet;
[0047] The method of warm pressing treatment is: the pressing pressure is 500MPa, the pressing time is 4min, and the pressing method is floating pressing;
[0048] The micro-etching process is laser micro-etching process, the laser energy is 1100mJ, the laser wavelength is 1075nm, and the pulse time is 14ns; the vapor deposition parameters are: power is 6000W, pressure is 190Pa, and the electrode spacing is 480 mils;
[0049] The preparation method of the mesoporous ceramic powder composite liquid loaded with octenidine is as follows: dissolving octenidine in acetone at a ratio of 30 g:500 mL to obtain an octenidine solution; then mixing the mesoporous ceramic powder and the octenidine solution at a mass ratio of 3:0.6, and then electromagnetically stirring at a temperature of 33°C for 24 minutes; the electromagnetic power is 30 W, the magnetic strength is 150 T, and the rotation speed is 350 r / min to obtain a mesoporous ceramic powder composite liquid loaded with octenidine; wherein the mesoporous ceramic powder adopts a mesoporous silica powder with a particle size of 2 to 50 nm commercially available from Beijing Zhongke Keyou Technology Co., Ltd.;
[0050] The coating method is a combination of spin coating and dip coating.
[0051] The method of coordinated treatment of spin coating and dip coating is as follows: during the first 7 / 24 of the coating thickness, the micro-etched warm pressed blank is fixed on the tray of the spin coater, the spin coater is started and rotated at a first speed for 2 minutes, and at the same time, 5 / 12 of the mesoporous ceramic powder composite liquid loaded with octenidine is taken and dripped on the top of the spin coater at a flow rate of 4 mL / s, and after dripping, the spin coater is adjusted to rotate at a second speed for 3 minutes, and the first oxide layer is obtained by heating; wherein the first speed is 40 r / min, the second speed is 1800 r / min, the heating temperature is 88°C, and the heating time is 8 minutes;
[0052] Then, the blank loaded with the first oxide layer is vertically immersed in the remaining mesoporous ceramic powder composite liquid loaded with octenidine, and then vertically pulled up after standing for 22 seconds, and the dip coating is repeated 4 times to obtain a preset oxide layer; after each dip coating, a smoothing treatment is performed, and the smoothing treatment method is: using high-pressure nitrogen to flush the surface of the blank for 6 minutes, and then rinsing with deionized water for 3 times;
[0053] During the laser cladding process: the processing power was 20 W, the scanning speed was 600 mm / s, the time was 17 ns, and the loading amount of octenidine was 60%;
[0054] S3, cooling and cold rolling
[0055] The billet to be rolled is subjected to 5 passes of cooling cold rolling, with a temperature drop of 40°C in each pass, a deformation of 30% in each pass, and vacuum annealing between each pass to obtain the rolled billet; the vacuum annealing temperature is 680°C, the time is 25min, and the vacuum degree is 10 -1.2 Pa;
[0056] S4. Post-processing
[0057] After rolling, the titanium alloy foil is straightened and the surface is cleaned.
[0058] Example 2: Different from Example 1, in step S1, the vacuum degree in the vacuum melting furnace is 4.5 Pa, the arc stabilization current is 1 A, the melting voltage is 25 V, the melting current is 3 kA, and the melting time is 5 min.
[0059] Example 3: Different from Example 1, in step S1, the vacuum degree in the vacuum melting furnace is 4.5 Pa, the arc stabilization current is 3 A, the melting voltage is 35 V, the melting current is 5 kA, and the melting time is 15 min.
[0060] Embodiment 4: Different from Embodiment 1, in step S2, the ingot is heated to 480°C, kept at this temperature for 30 minutes, and then subjected to multi-fire warm pressing treatment, with a total processing rate of 60%, to obtain a warm pressed billet.
[0061] Example 5: Different from Example 1, in step S2, the ingot is heated to 520°C, kept warm for 60 minutes, and then subjected to multi-fire warm pressing treatment with a total processing rate of 80% to obtain a warm pressed billet.
[0062] Example 6: Different from Example 1, in step S2, the method of multi-fire warm pressing treatment is: continuously heating, and performing one pass of warm pressing treatment and keeping warm for 25 minutes when the temperature is raised to 70°C below the β transformation temperature of the ingot, 35°C below the β transformation temperature, 10°C below the β transformation temperature, 25°C above the β transformation temperature, and 50°C above the β transformation temperature, and performing one pass of multi-directional forging at each corresponding temperature to obtain a warm pressed billet; wherein the method of warm pressing treatment is: the pressing pressure is 450MPa, the pressing time is 5min, and the pressing method is bidirectional pressing.
[0063] Example 7: Different from Example 1, in step S2, the method of multi-fire warm pressing treatment is: continuously heating up, and performing one pass of warm pressing treatment and keeping warm for 30 minutes when the temperature is raised to 80°C below the β transformation temperature of the ingot, 45°C below the β transformation temperature, 15°C below the β transformation temperature, 40°C above the β transformation temperature, and 60°C above the β transformation temperature, and performing one pass of multi-directional forging at each corresponding temperature to obtain a warm pressed billet; wherein, the method of warm pressing treatment is: the pressing pressure is 550MPa, the pressing time is 3min, and the pressing method is floating pressing.
[0064] Embodiment 8: Different from Embodiment 1, in the laser micro-etching process of step S2, the laser energy is 1000 mJ, the laser wavelength is 1050 nm, and the pulse time is 12 ns.
[0065] Embodiment 9: Different from Embodiment 1, in the laser micro-etching process of step S2, the laser energy is 1200 mJ, the laser wavelength is 1100 nm, and the pulse time is 16 ns.
[0066] Example 10: Different from Example 1, in step S2, the preparation method of the mesoporous ceramic powder composite liquid loaded with octenidine is as follows: dissolve octenidine in acetone at a ratio of 25g:400mL to obtain an octenidine solution; then mix the mesoporous ceramic powder and the octenidine solution at a mass ratio of 1:0.5, and then stir electromagnetically at a temperature of 30°C for 23 minutes; the electromagnetic power is 25W, the magnetic strength is 100T, and the rotation speed is 200r / min to obtain a mesoporous ceramic powder composite liquid loaded with octenidine; in this embodiment, the mesoporous ceramic powder is commercially available mesoporous yttrium oxide Y2O3 powder with a particle size of 2 to 50nm.
[0067] Example 11: Different from Example 1, in step S2, the preparation method of the mesoporous ceramic powder composite liquid loaded with octenidine is as follows: dissolve octenidine in acetone at a ratio of 40g:600mL to obtain an octenidine solution; then mix the mesoporous ceramic powder and the octenidine solution at a mass ratio of 5:0.7, and then stir electromagnetically at a temperature of 35°C for 25 minutes; the electromagnetic power is 40W, the magnetic strength is 200T, and the rotation speed is 500r / min to obtain a mesoporous ceramic powder composite liquid loaded with octenidine; in this embodiment, the mesoporous ceramic powder uses mesoporous ZrO2-SiO2 powder with a particle size of 2 to 50nm.
[0068] Embodiment 12: Different from Embodiment 1, in step S2, the method of coordinated treatment is: during the first 1 / 4 of the coating thickness, the micro-etched warm pressed blank is fixed on the tray of the spin coater, the spin coater is started and rotated at the first speed for 1 min, and at the same time, 1 / 3 of the mesoporous ceramic powder composite liquid loaded with octenidine is taken and dripped on the top of the spin coater at a flow rate of 3 mL / s, and after dripping, the spin coater is adjusted to rotate at the second speed for 2 to 5 minutes, and the first oxide layer is obtained by heating; wherein the first speed is 30 r / min, the second speed is 1500 r / min, the heating temperature is 85°C, and the heating time is 5 min;
[0069] The blank loaded with the first oxide layer is then vertically immersed in the remaining mesoporous ceramic powder composite liquid loaded with octenidine, and is vertically pulled up after standing for 20 to 25 seconds. The dipping is repeated 3 to 5 times to obtain a preset oxide layer. After each dipping, a smoothing treatment is performed. The smoothing treatment method is: use high-pressure nitrogen to flush the surface of the blank for 5 to 8 minutes, and then rinse with deionized water 2 to 4 times.
[0070] Embodiment 13: Different from Embodiment 1, in step S2, the method of coordinated treatment is: during the first 1 / 3 of the coating thickness, the warm pressed blank after micro-etching treatment is fixed on the tray of the spin coater, the spin coater is started and rotated at the first speed for 3 minutes, and at the same time, 1 / 2 of the mesoporous ceramic powder composite liquid loaded with octenidine is taken and dripped on the top of the spin coater at a flow rate of 5 mL / s, and after dripping, the spin coater is adjusted to rotate at the second speed for 5 minutes, and the first oxide layer is obtained by heating; wherein the first speed is 50 r / min, the second speed is 2000 r / min, the heating temperature is 90°C, and the heating time is 10 min;
[0071] The blank loaded with the first oxide layer is then vertically immersed in the remaining mesoporous ceramic powder composite liquid loaded with octenidine, and then vertically pulled up after standing for 25 seconds. The dipping is repeated 5 times to obtain a preset oxide layer. After each dipping, a smoothing treatment is performed. The smoothing treatment method is: use high-pressure nitrogen to flush the surface of the blank for 8 minutes, and then rinse with deionized water 4 times.
[0072] Example 14: Different from Example 1, in the laser cladding process of step S2: the processing power is 18 W, the scanning speed is 500 mm / s, the time is 15 ns, and the loading amount of octenidine is 58%.
[0073] Example 15: Different from Example 1, in the laser cladding process of step S2: the processing power is 22 W, the scanning speed is 700 mm / s, the time is 18 ns, and the loading amount of octenidine is 62%.
[0074] Example 16: Different from Example 1, in step S3, the billet to be rolled is subjected to three passes of cooling and cold rolling, with each pass reducing the temperature by 30°C, each pass causing a deformation of 15%, and vacuum annealing is performed between each pass to obtain a rolled billet.
[0075] Example 17: Different from Example 1, in step S3, the billet to be rolled is subjected to 8 passes of cooling and cold rolling, with a temperature reduction of 50°C in each pass, a deformation of 40% in each pass, and vacuum annealing between each pass to obtain a rolled billet.
[0076] Embodiment 18: Different from Embodiment 1, in step S3, the vacuum annealing temperature is 650°C, the time is 20 min, and the vacuum degree is 10 -2 Pa.
[0077] Example 19: Different from Example 1, in step S3, the vacuum annealing temperature is 700°C, the time is 30 min, and the vacuum degree is 10 -1 Pa.
[0078] Experimental Example: The description of this experimental example is based on the scheme described in Example 1, and is intended to illustrate the practical application effect of the present invention;
[0079] Corrosion resistance test: According to the national standard GB6458-86 for salt spray corrosion, this test uses 5wt% neutral NaCl corrosion liquid, the pH value of the corrosion liquid in the salt spray chamber is measured to be 6.9, the experimental temperature is set at about 35°C, and the test adopts continuous spray mode.
[0080] Salt spray corrosion test parameters: test cycle is 15 days, spray speed is 0.025mL·cm -2 ·h -1 , pressure is 0.08~0.15Mpa, relative humidity is 90~98%. The test specimens should be placed at a distance to ensure that the salt spray can settle freely on all specimen surfaces. 2 The surface area must be able to collect 1 to 2 mL of salt solution every hour, and the NaCl mass fraction must be within 4 to 6 wt%.
[0081] After 15 days of salt spray corrosion, the titanium alloy sample was cleaned and weighed with deionized water. The weighing was carried out using an analytical balance with an accuracy of 0.1 mg. The results are as follows:
[0082] 1. Investigate the influence of the process parameters of titanium alloy ingot preparation and warm pressing billet process parameters on the corrosion resistance of titanium alloy foil
[0083] Control group 1: Different from Example 1, the temperature pressing treatment below the β-transus temperature is not performed.
[0084] Control group 2: Different from Example 1, no heat preservation is performed after each warm-pressing treatment.
[0085] Conclusion: Figure 1 From the comparison of Examples 1 to 7, it can be seen that excessive or insufficient process parameters in the preparation process of titanium alloy ingots will affect the corrosion resistance of the titanium alloy foil. From the perspective of comprehensive corrosion resistance, the scheme in Example 1 is better, and from the comparison of Examples 1 to 5 and Control Group 1, it can be seen that the control group 1 is not effective in maintaining the good plasticity and deformation ability of the titanium alloy without performing warm pressing below the β transformation temperature, which makes the titanium alloy more easily deformed during the subsequent rolling process, thereby reducing the corrosion resistance of the titanium alloy. From the comparison of Examples 1, 6 to 7 and Control Group 2, it can be seen that the corrosion resistance of the titanium alloy foil in Control Group 2 has declined significantly. The main reason may be that the thermal insulation and aging treatment can refine and disperse the precipitated phase in the titanium alloy, further improve the heat resistance and oxidation resistance of the titanium alloy, form a more stable intergranular phase, thereby improving the oxidation resistance and heat resistance of the material.
[0086] 2. Investigate the effect of composite coating preparation method on the corrosion resistance of titanium alloy foil
[0087] Control group 3: Different from Example 1, the mesoporous ceramic powder solution loaded with octonidine was replaced with a commercially available ceramic dispersion.
[0088] Control group 4: Different from Example 1, the surface of the blank after micro-etching treatment is directly coated by dipping.
[0089] Control group 5: Different from Example 1, no smoothing treatment was performed after the dip coating was completed.
[0090] Conclusion: Figure 2 From the comparison of Example 1 and Examples 8 to 15, it can be seen that the process parameters of laser micro-etching treatment are too large or too small, the preparation parameters of the mesoporous ceramic powder composite liquid loaded with octonidine are too large or too small, the parameters in the spin coating and dip coating coordinated coating process are too large or too small, and the laser dissolution parameters are too large or too small, which will have a slight effect on the performance of the titanium alloy foil. The titanium alloy foil prepared under the parameters of Example 1 has better corrosion resistance, while from the comparison of Example 1, Examples 10 to 11 and Control Group 3, it can be seen that the corrosion resistance of the ceramic dispersion is also significantly weakened. This shows that octonidine loaded in the mesoporous ceramic powder can be more effectively released and attached to the surface of the titanium alloy foil to form an antibacterial barrier, further preventing the growth and reproduction of corrosion bacteria, thereby enhancing the corrosion resistance of the titanium alloy. Corrosion resistance of gold foil; By comparing Example 1, Example 12 to Example 13 and Control Group 4 and Control Group 5, it can be seen that directly coating the surface of the blank after micro-etching by dip coating and not smoothing after dip coating will also affect the corrosion resistance of titanium alloy foil. The main reason is that the spin coating treatment in the early stage of coating can fill and partially seal the micropores, thereby reducing the chance of corrosive media such as water and oxygen directly contacting the titanium alloy substrate, further improving its corrosion resistance, and the smoothing treatment can use the flushing of high-pressure nitrogen to remove loose particles and tiny defects on the coating surface, making the coating smoother and tighter. Through the combination of spin coating, dip coating and subsequent smoothing treatment, the bonding force between the coating and the titanium alloy foil substrate is enhanced. The dense coating can further improve the overall density and stability of the titanium alloy foil, and can also reduce the possibility of corrosive medium penetration, further improving the corrosion resistance.
[0091] 3. Investigate the effect of cooling and cold rolling process parameters on the corrosion resistance of titanium alloy foil
[0092] Control group 6: Different from Example 1, a vacuum annealing was performed after the cold rolling was completed.
[0093] Conclusion: Figure 3A comparison of Example 1, Examples 16 to 19 and Control Group 6 shows that only one vacuum annealing may not be able to completely remove all surface defects and contaminants generated during the cold rolling process, so the corrosion resistance of the titanium alloy foil obtained in Control Group 6 is weakened. The combined effect of cooling cold rolling and vacuum annealing in the present application helps to refine the grain structure of the titanium alloy foil and reduce cracks and pores in the titanium alloy foil. The finer the grains, the more cracks and pores form the grain boundaries, the more tortuous the diffusion path of the corrosive medium, thereby improving the corrosion resistance of the material. Therefore, considering all factors, Example 1 is the best solution.
Claims
1. A method for preparing a corrosion-resistant titanium alloy foil for a plate heat exchanger, characterized in that: The following steps are involved: S1. Preparation of titanium alloy ingots Weighing raw materials, and performing vacuum induction melting on the raw materials to obtain a titanium alloy ingot; S2. Preparation of billet to be rolled The ingot is heated to 480-520°C, kept warm for 30-60 minutes, and then subjected to multi-fire warm pressing treatment, with a total processing rate of 60-80%, to obtain a warm pressed blank, and the surface of the warm pressed blank is micro-etched to produce a plurality of micropores with an aperture of 0.01-0.03 mm on the surface, and then boron oxide particles are vapor-deposited inside the micropores, and a mesoporous ceramic powder composite liquid loaded with octenidine is coated on the surface of the warm pressed blank to obtain a preset oxide layer with a thickness of 0.03-0.05 mm, a protective atmosphere is introduced, and laser cladding and nickel plating are performed, and after completion, a blank to be rolled with a composite film layer on the surface is obtained; During the laser cladding process: the processing power is 18-22W, the scanning speed is 500-700mm / s, the time is 15-18ns, and the loading amount of octenidine is 58-62%; S3, cooling and cold rolling The billet to be rolled is subjected to 3 to 8 passes of cooling cold rolling, with each pass cooling 30 to 50°C, each pass deformation of 15 to 40%, and vacuum annealing between each pass to obtain the rolled billet; the vacuum annealing temperature is 650 to 700°C, the time is 20 to 30 minutes, and the vacuum degree is 10 -2 ~10 -1 Pa; S4. Post-processing After rolling, the titanium alloy foil is straightened and the surface is cleaned.
2. The method for preparing a corrosion-resistant titanium alloy foil for a plate heat exchanger according to claim 1, characterized in that: The preparation method of the mesoporous ceramic powder composite liquid loaded with octenidine is as follows: dissolving octenidine in acetone at a ratio of 25 to 40 g: 400 to 600 mL to obtain an octenidine solution; then mixing the mesoporous ceramic powder and the octenidine solution at a mass ratio of 1 to 5: 0.5 to 0.7, and then electromagnetically stirring for 23 to 25 minutes at a temperature of 30 to 35° C.; the electromagnetic power is 25 to 40 W, the magnetic strength is 100 to 200 T, and the rotation speed is 200 to 500 r / min to obtain the mesoporous ceramic powder composite liquid loaded with octenidine.
3. The method for preparing a corrosion-resistant titanium alloy foil for a plate heat exchanger according to claim 2, characterized in that: The coating method is a coordinated process of spin coating and dip coating. The method for the coordinated treatment of spin coating and dip coating is as follows: during the first 1 / 4 to 1 / 3 of the coating thickness, the micro-etched warm pressed blank is fixed on the tray of the spin coater, the spin coater is started and rotated at a first speed for 1 to 3 minutes, and at the same time, 1 / 3 to 1 / 2 of the mesoporous ceramic powder composite liquid loaded with octenidine is taken and dripped on the top of the blank at a flow rate of 3 to 5 mL / s, and after dripping, the spin coater is adjusted to rotate at a second speed for 2 to 5 minutes, and the first oxide layer is obtained by heating; wherein the first speed is 30 to 50 r / min, the second speed is 1500 to 2000 r / min, the heating temperature is 85 to 90° C., and the heating time is 5 to 10 minutes; Then the blank loaded with the first oxide layer is vertically immersed in the remaining mesoporous ceramic powder composite liquid loaded with octenidine, and is vertically pulled up after standing for 20 to 25 seconds, and the dipping is repeated 3 to 5 times to obtain a preset oxide layer.
4. The method for preparing a corrosion-resistant titanium alloy foil for a plate heat exchanger according to claim 3, characterized in that: After each dip coating, a smoothing treatment is performed. The smoothing treatment method is: flushing the surface of the blank with high-pressure nitrogen for 5 to 8 minutes, and then rinsing with deionized water for 2 to 4 times.
5. The method for preparing a corrosion-resistant titanium alloy foil for a plate heat exchanger according to claim 1, characterized in that: In step S2, the method of the multi-fire warm pressing treatment is: continuously heating, and performing one pass of warm pressing treatment and keeping the temperature for 25 to 30 minutes when the temperature is raised to 70 to 80°C below the ingot β transformation temperature, 35 to 45°C below the β transformation temperature, 10 to 15°C below the β transformation temperature, 25 to 40°C above the β transformation temperature, and 50 to 60°C above the β transformation temperature, respectively, and performing one pass of multi-directional forging at each corresponding temperature to obtain the warm pressed billet; The method of the warm pressing treatment is as follows: the pressing pressure is 450-550 MPa, the pressing time is 3-5 min, and the pressing method is bidirectional pressing or floating pressing.
6. The method for preparing a corrosion-resistant titanium alloy foil for a plate heat exchanger according to claim 1, characterized in that: In step S1, during the vacuum induction melting, the vacuum degree in the vacuum melting furnace is ≤4.5 Pa, the arc stabilization current is 1-3 A, the melting voltage is 25-35 V, the melting current is 3-5 kA, and the melting time is 5-35 min.
7. The method for preparing a corrosion-resistant titanium alloy foil for a plate heat exchanger according to claim 1, characterized in that: In step S2, the micro-etching process is laser micro-etching process, the laser energy is 1000-1200 mJ, the laser wavelength is 1050-1100 nm, and the pulse time is 12-16 ns.
8. The method for preparing a corrosion-resistant titanium alloy foil for a plate heat exchanger according to claim 1, characterized in that: In step S2, the vapor deposition parameters are: power of 5000-7000 W, pressure of 180-200 Pa, and electrode spacing of 400-550 mils.
Citation Information
Patent Citations
Titanium alloy composite material coated with composite coating and preparation method and application of titanium alloy composite material
CN105458271A
Novel beta-type titanium alloy low-modulus high-precision ultrafine crystal foil preparation method
CN108929962A
Hydrophilic aluminum foil production technology for air conditioner
CN111389693A
Magnesium-aluminum composite board for building and preparation method of magnesium-aluminum composite board
CN115975406A
Method of producing protective corrosion-resistant biocompatible hybrid coating on magnesium alloy
RU2815770C1